Mass attenuation coefficients and Range of β- Particles in Aluminum and Gold: A Comparison study - Ali Mahdi Ahmed; Faris Salih Ata Allah; Sabah Mahmoud Aman Allah (Tikrit Journal of Pure Science)
Beta particle has a huge applications in industry,  medicine and research fields. The aim of the present study is to calculate the mass attenuation coefficients  (μ / ρ)β_ and the range of Rβ- for negative beta particles within the energy range (0.257-2.25) MeV for 13Al and 79Au respectively. Use the equation of Kisse and Vertes to calculate the mass attenuation coefficient and the Tabata equations to calculate the range of electrons in the same elements. All the equations were adopting by the program (Visual studio professional 2012). The results we obtained were compared with the available experimental one, indicating that they are in good agreement, thus supporting the possibility of applying them to other elements effectively. As for the range it is a function of the negative beta particle energy and then the range in the aluminum is greater than the of the values in gold due to the electronic density of the gold element.